Pelestarian Budaya Lokal Dalam Media Pembelajaran Berbasis Proyek Simulasi (PBPS) Pada Generasi Milenial - Zulfa Zulfa; Desri Nora; Refni Yulia; Edi Susrianto Indra Putra (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2022)
The younger generation increasingly does not love local culture. This is proven by the existence of increasingly sophisticated technology. The change in learning during the Covid period from face-to-face to online has increasingly made the younger generation less interested in learning anything. Meanwhile, preserving local culture is very important for this millennial generation. Simulation project-based learning (PBPS) is a learning model that will awaken a generation's love for local cultural traditions. The purpose of this study is to reveal efforts to preserve local culture in Simulation Project Based Learning (PBPS) media. This research method is to use qualitative research methods by analyzing data with reduction, data presentation and verification. The results of this study revealed that the simulation project-based learning model was carried out in 6 steps, namely: Determining Fundamental Questions (Start with the Essential Question). Designing Project Planning (Design a Plan for the Project). Testing the Results (Assess the Outcome). Implementation of Simulation (Simulation). Interviewing Students and the Progress of the Project (Monitor the Students and the Progress of the Project). Evaluate the Experience (Evaluate the Experience). Of the six steps in this PBPS, it is carried out in every existing studio. By carrying out this PBPS for 8 meetings, efforts to preserve local culture will be realized in the millennial generation.